"My Name is A-on-the-cheek": Managing Names and Name Signs in American Sign Language-English Team Interpretation. (2nd October 2018) - Petitta, Giulia; Dively, Valerie; Halley, Mark; Holmes, Marc; Nicodemus, Brenda
Abstract : Interpreters face challenges when rendering names between languages. First, names may be unknown to the interpreter or contain culturally specific information. Further, names lack contextual clues that aid the decoding process. Finally, names may be pronounced in a manner that is difficult to understand (e.g., rapidly or with an accent). Spoken language interpreters have the option of repeating names in their original form; however, signed language interpreters work between languages produced in distinct language modalities (sign-speech) that share no phonological features; thus, names cannot simply be reproduced across languages. In this study we created a mock scenario between two interlocutors (a hearing computer specialist and a deaf international student) who enacted a training session in which they deliberately incorporated names. The interlocutors repeated this training session three times, each with a different team of interpreters. We report strategies used by the teams to convey names in their interpretations.